Pelatihan Budidaya Jamur Tiram Putih Menggunakan Bibit F1 Desa Bawuran Pleret Bantul - Ubaidillah Ubaidillah (Humanism: Journal of Community Empowerment (HJCE), 2020)
Mushroom cultivation is a promising business because it is in great demand to be used as a food consumption such as oyster mushrooms and mushroom mushrooms. Oyster mushroom is a type of fungus that lives on weathered wood, sawdust ,. This organism is in great demand because of its high nutritional content and very good benefits. Because the nutritional content is very good, many people who use it for cultivation, besides having good selling points and relatively easy cultivation techniques. This sawdust waste is the raw material for white oyster mushrooms. With its abundant availability, this white oyster mushroom growing medium can be made as much as possible for cultivation that is very prospective for development. F1 seedlings that are often used in nurseries are pure culture subcultures. The advantage of using F1 seeds is that the mycelium is still very strong, so that later oyster mushrooms growing on baglog can be more numerous and the production results will also be more numerous . This community service activity is motivated by the large amount of sawdust waste found in many villages. Therefore, a white oyster mushroom cultivation business was arranged. The purpose of this community service activity is to provide skills to the community by cultivating oyster mushrooms using F1 seeds. The method to be carried out is the preparation, implementation and evaluation stages. In the preparation stage, what is done is preparing tools and materials. In the implementation phase of the service, the program will start from making F1 seeds at the D-3 Pharmacy Laboratory Instrument at Solar Global Stikes. Finally, the evaluation stage will see the results of the growth of the fungus misellium, the process of making baglog to the harvesting process